Pengaruh Digitalisasi, Perencanaan Pajak, Struktur Modal, Dan Kepemilikan Manajerial Terhadap Nilai Perusahaan Dengan Transparansi Perusahaan Sebagai Variabel Moderasi - Haq, Naufal Rizqi; Ardhani, Lutfi (Gorontalo Accounting Journal, 2025)
This research analyzes the influence of digitalization, tax planning, capital structure and managerial ownership on company value with company transparency as a moderating variable with the research object being consumer goods sector companies listed on the Indonesia Stock Exchange IDXI) in 2021. The sample for this research is 65 companies. with a total of 193 data. The data analysis technique used in this research is linear regression analysis technique. The research results show that digitalization, tax planning and managerial ownership have no effect on company value. Meanwhile, capital structure influences company value. Company transparency is unable to moderate the relationship between digitalization, tax planning, capital structure and managerial ownership on company value.